A revision of the North Atlantic amphipod genus Normanion (Crustacea: Amphipoda: Lysianassoidea) - Niamh, Niamh M.; Myers, Alan A.; Mcgrath, David (Zootaxa, 2006)
Members of the lysianassoid genus Normanion have previously been difficult to identify, due to uncertainty regarding synonymies and validity among members of the taxon. Here, the genus is reviewed and a full description with illustrations is provided for the four eyed-species. Species are compared and synonymies are resolved.